Are Accounting Undergraduates Apprehensive About Oral Communication - Minai, Badriyah; Salleh, Arfah (Universiti Putra Malaysia Press, 1997)
Communication has been identified as one of the skills required to become successful professional accountants (IFAC 1994; AAA 1990). Studies have shown that the ability to communicate effectively has been hampered by the level of oral communication apprehension (OCA) (McCroskey, 1977a; Freimuth, 1976). This study investigates the incidence of OCA amongst accounting students at Universiti Putra Malaysia. It compares OCA level in terms of gender, seating position and participation in co-curricular activities. OCA level is operationalized using Personal Report of Communication Apprehension developed by McCroskey (1984). Adopting the t-test to determine differences in OCA level between groups, it is found that males do not differ significantly from females. In terms of seating position, it is observed that respondents who prefer the front and middle seats are significantly less apprehensive about communicating in group context only than those who choose the seats on the side and back of the classroom. Overall, there is no difference between OCA level of students according to seating position. The results also reveal that significant difference exists between undergraduates who participate in co-curricular activities at university level and those who do not.